Benefits of Cardiac Rehabilitation on Cardiovascular Outcomes in Patients With Diabetes Mellitus After Percutaneous Coronary Intervention - Jiménez‐Navarro, Manuel F.; Lopez‐Jimenez, Francisco; Pérez‐Belmonte, Luis M.; Lennon, Ryan J.; Diaz‐Melean, Carlos; Rodriguez‐Escudero, J. P.; Goel, Kashish; Crusan, Daniel; Prasad, Abhiram; Squires, Ray W.; Thomas, Randal J. (Journal of the American Heart Association, 2017)
Background Participation in cardiac rehabilitation (CR) is an essential component of care for patients with coronary artery disease. However, little is known about its benefit on cardiovascular outcomes in patients with diabetes mellitus (DM) who have undergone percutaneous coronary intervention. The aim of our study was to evaluate the impact of CR in this high‐risk group of patients. Methods and Results We performed a retrospective analysis of all patients with DM who underwent percutaneous coronary intervention in Olmsted County (Minnesota) between 1994 and 2010, assessing the impact of CR participation on clinical outcomes. CR participation was significantly lower in patients with DM (38%, 263/700) compared with those who did not have DM (45%, 1071/2379; P=0.004). Using propensity score adjustment, we found that in patients with DM, CR participation was associated with significantly reduced all‐cause mortality (hazard ratio, 0.56; 95% confidence interval, 0.39–0.80; P=0.002) and composite end point of mortality, myocardial infarction, or revascularization (hazard ratio, 0.77; 95% confidence interval, 0.60–0.98; P=0.037), during a median follow‐up of 8.1 years. In patients without DM, CR participation was associated with a significant reduction in all‐cause mortality (hazard ratio, 0.67; 95% confidence interval, 0.55–0.82; P<0.001) and cardiac mortality (hazard ratio, 0.67; 95% confidence interval, 0.47–0.95; P=0.024). Conclusions CR participation after percutaneous coronary intervention is associated with lower all‐cause mortality rates in patients with DM, to a similar degree as for those without DM. However, CR participation was lower in patients with DM, suggesting the need to identify and correct the barriers to CR participation for this higher‐risk group of patients.